Development of Augmented Reality Teaching Modules on Material Understanding Human Respiratory Organs Class V Elementary School - Riduan, Ahmad; Ida Suryani; Patricia H.M. Lubis (Elementary Teacher Education Program, Majalengka University, 2024)
This research is a form of investigative research and development (R&D). This research uses the ADDIE research model, which includes five different stages: analysis, design, development, implementation, and evaluation. This study involved fifth grade students at SD Negeri 7 Muara Telang. Data collection methods used include interviews, questionnaires, and documentation. Validity analysis and practicality analysis. The validation analysis procedures were assessed by three experts, namely material experts, media experts, and language experts. The average level of validity was determined to be 92.66%, indicating a high level of validity. The practicality analysis procedure was evaluated by carrying out individual tests on 3 students at the initial stage, followed by small group tests involving 8 students. The test results gave an average score of 92.08%, which shows a high level of practicality. As a result, it can be concluded that the augmented reality teaching module, which focuses on teaching fifth grade students about the introduction of human respiratory organs, is very valid and practical, making it suitable for use in the classroom.